2023
DOI: 10.3390/jcm12062131
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia Exacerbates Meibomian Gland Dysfunction: A Systematic Review and Meta-Analysis

Abstract: Dry eye is a multifactorial and common age-related ocular surface disease. Dyslipidemia has been reported to be involved in meibomian gland dysfunction (MGD). However, it has not been clearly identified which lipid abnormality is responsible for MGD. In this systematic review and meta-analysis, we discuss how lipid profile changes with aging is responsible for MGD development. Methods. An article search was performed in PubMed, EMBASE, and Web of Science. Eleven studies involving dyslipidemia in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“… 19 , 38 Clinical studies linked hypercholesterolemia and MGD. 51 53 Considering that blood Chl can be transported to, and accumulated in, MGs in unaltered form, these observations provide an opportunity for Chl to play a role in inspissation of meibum of certain types of MGD (e.g. its obstructive variant) and patients with DED, and poor stability of their TF.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 38 Clinical studies linked hypercholesterolemia and MGD. 51 53 Considering that blood Chl can be transported to, and accumulated in, MGs in unaltered form, these observations provide an opportunity for Chl to play a role in inspissation of meibum of certain types of MGD (e.g. its obstructive variant) and patients with DED, and poor stability of their TF.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, Aldaas et al reviewed 72,931 patients to study the association between DES and dyslipidemia and found that the odds of having a DES diagnosis are increased in patients with dyslipidemia [ 26 ]. In a meta-analysis, Tomoika et al showed that high total cholesterol and high triglycerides were significantly associated with meibomian gland dysfunction and dry eyes, with odds ratios of 5.2 and 3.2, respectively [ 27 ]. Other studies showed similar results, with a higher incidence of DES in patients with dyslipidemia [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, PE is also an important phospholipid in the cell membranes of mammals and is required for the stability of lipoproteins. 55 Dyslipidemia is one of the significant risk factors for MGD. 56 The proportions of PE (4.6 ± 3.2 vs. 16.7 ± 4%, P < 0.05) and SM (7.2 ± 4.8 vs. 14.0 ± 8.1%, P < 0.05) in patients with chronic blepharitis-keratoconjunctivitis sicca (CB-KCS) were significantly reduced compared with normal controls, respectively.…”
Section: Discussionmentioning
confidence: 99%